A case report of Kuttner tumor mimicking a malignant tumor, leading to overtreatment. Issue 5 (6th May 2021) - Baba, Daisuke; Sotome, Keiichi; Maeda, Ichiro; Takabayashi, Kosuke; Kiyomizu, Kensuke; Nakayama, Meiho; Ogawa, Kaoru
Abstract: Preoperative diagnosis with multimodal approaches might lead to overtreatment. Cautious understanding of cytology and dynamic contrast‐enhanced magnetic resonance imaging is required when a Kuttner tumor is cited as differential diagnosis. Abstract : Preoperative diagnosis with multimodal approaches might lead to overtreatment. Cautious understanding of cytology and dynamic contrast‐enhanced magnetic resonance imaging is required when a Kuttner tumor is cited as differential diagnosis.